Virtual Community Engagement for Retention of Black Men in Clinical Research. Issue 1 (January 2023) - Nolan, Timiya S.; McKoy, Alicia; Gray, Darrell M.; Metlock, Faith; Addison, Sarah; Ogonuwe, Stephanie S.; Gregory, John; Lavender, Dana; Reopell, Luiza; Joseph, Joshua J.
Black American men have worse cardiovascular health compared with their White counterparts, yet are highly underrepresented in clinical trials. In 2020, Black men were recruited to participate in Black Impact, a community-based lifestyle intervention to increase cardiovascular health. Due to the research pause during the Coronavirus Disease (COVID-19) pandemic, a virtual community engagement (VCE) process was co-designed with community stakeholders and evaluated for its effect on retention for the clinical trial. VCE via weekly virtual video conference sessions occurred for 9 weeks as a run-in phase prior to in-person research activities. Data collected during sessions included attendance, anecdotes on acceptability, and topical requests for subsequent weeks. Content analysis was performed on scribe notes from sessions to ascertain themes describing the implementation and participant perceptions of the VCE. Descriptive statistics were used to analyze quantitative data. The VCE provided opportunities to co-create a safe atmosphere in small groups, discuss mental health, foster trust, capitalize on the power of spirituality, and establish a brotherhood. Following the VCE run-in phase, 74 of 100 participants remained engaged for participation in the Black Impact study. The VCE described provides a framework that can be used to retain Black men during study delays or disruptions through fostering engagement and building community among participants and researchers.